Penyuluhan Tentang Cuci Tangan Di SD Pakutandang I Ciparay Tahun 2021 - Fitri Komalasari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
The most effective and simple way to remove germs from your hands is to wash your hands with clean water and use soap. The method used in this community service activity is to provide education about washing hands with soap properly through seven steps for good and correct washing. The results of implementing service activities can be described through 2 (two) activity stages, namely preparation and implementation. Students listened to an explanation about the importance of washing hands properly using soap and running water, and 30 students were able to practice the correct way of washing hands, so that they can be applied in everyday life, such as washing hands with soap after playing, eating and after eating. This activity can make a positive contribution in reducing and preventing health problems, especially in the Pacet area, Bandung Regency